1993
DOI: 10.1073/pnas.90.21.9988
|View full text |Cite
|
Sign up to set email alerts
|

D-chiro-inositol metabolism in diabetes mellitus.

Abstract: D-chiro-Inositol is a rare inositol isomer present in inositol phosphoglycans which are proposed mediators of insulin action. To study D-chiro-inositol metabolism in diabetes mellitus, a sensitive and specific assay was developed using negative-ion chemical ionization gas chromatography/mass spectrometry. Median urinary D-chiro-inositol excretion, which was 2.1 ,umol/day in nondiabetics, was substantially increased to 12 ,umol/day in non-insulin-dependent diabetes (P < 0.0001) and to 74 j,mol/day in insulin-de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
140
6
3

Year Published

1995
1995
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(159 citation statements)
references
References 11 publications
10
140
6
3
Order By: Relevance
“…Moreover, bioactivity of the pH 2.0 IPG isolated from haemodialysate, urine and muscle from NIDDM patients was attenuated vs control [9]. On the other hand, Ostlund et al [23] showed that patients with NIDDM, as well as insulin-dependent diabetes IDDM, excreted substantially more d -chiro-inositol in urine than obese nondiabetic patients (control group), while plasma d -chiro-inositol levels were similar among the three groups. The possibility exists, however, that the obese non-diabetic patients were insulin resistant [24], and therefore were not appropriate control subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, bioactivity of the pH 2.0 IPG isolated from haemodialysate, urine and muscle from NIDDM patients was attenuated vs control [9]. On the other hand, Ostlund et al [23] showed that patients with NIDDM, as well as insulin-dependent diabetes IDDM, excreted substantially more d -chiro-inositol in urine than obese nondiabetic patients (control group), while plasma d -chiro-inositol levels were similar among the three groups. The possibility exists, however, that the obese non-diabetic patients were insulin resistant [24], and therefore were not appropriate control subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the K m for glucose is well above normal serum glucose levels. It seems clear that MI is the physiological substrate for the protein; although D-chiro-inositol is transported as readily as MI, the average serum level of D-chiroinositol is less than 100 nM (38), and thus D-chiro-inositol transport represents a minor physiological role for SMIT2. It should be noted that there has been one previous publication suggesting the names SMIT1, SMIT2, and SMIT3 for three alternate transcripts from the SLC5A3 gene (39); we suggest that these be named SMIT1a, SMIT1b, and SMIT1c, in which we have the consent of the authors of that work.…”
Section: Fig 6 Phlorizin Inhibition Of MI Currentmentioning
confidence: 99%
“…[106] The urinary excretion of D-chiro-inositol has been measured at 2.1 μmol/day in nondiabetics, but increases six-fold in non-insulin-dependent diabetics and another six-fold in insulindependent diabetics. [107] In a rat model of type 1 diabetes and a mouse model of type 2 diabetes the urinary excretion of D-chiro-inositol was much greater than in healthy rats and mice. [108] These studies contradict earlier work showing a lower urinary excretion (and lower muscle content) of D-chiro-inositol in non-insulin-dependent diabetics than in nondiabetics.…”
Section: D-chiro-inositol Diabetes Pregnancy and Polycystic Ovary Smentioning
confidence: 95%
“…[48] Between nondiabetics and noninsulin-dependent diabetics there was little difference in the urinary excretion of L-chiroinositol, but excretion increased just over three-fold, to 0.51 μmol/day, in insulin-dependent diabetics. [107] The non-mammalian biology of L-chiro-inositol is discussed in the Supporting Information (SI_2).…”
Section: Biologymentioning
confidence: 99%